Insect antiviral Mx-like protein forms biomolecular condensates to promote viral capsid ubiquitinated degradation - Yu Du; You Li; Yuqing Xiao; Dongsheng Jia; Taiyun Wei (Cell Reports)
Summary: Insects transmit diverse arthropod-borne viruses. However, it remains largely unknown whether insect innate immune pathways regulate the expression of antiviral factors to mediate the degradation of viral capsids. Here, we discover that transcription factor Dorsal in leafhopper Toll immune pathway binds to the promoter of vertebrate homolog myxovirus resistance-like (MxL) protein to activate its transcription. MxL associates with two different viral particles, promoting ubiquitinated degradation of viral capsids via E3 ubiquitin ligase SIAH1. Notably, MxL forms biomolecular condensates to recruit capsid protein P8 of a destructive rice reovirus and SIAH1. The disordered N-terminal region of MxL is essential for condensate formation. The Arg residue at position 159 of MxL is essential for MxL-P8 interaction and P8 recruitment into condensates. Viral nonstructural protein Pns11 interacts with Dorsal, effectively blocking its nuclear translocation and attenuating antiviral MxL1 expression. Our finding represents the first evidence that MxLs in invertebrates possess broad-spectrum antiviral functions.